Fully Biobased Composite from Lignocellulosic Plantain Waste with Potential Use in the Manufacture of Lollipop Sticks - Juan Pablo Castañeda-Niño; Lina Gisselth Ospina-Aguilar; Yean Carlos Zapata-Diaz; Robin Octavio Zuluaga-Gallego; Johanna Andrea Serna-Jiménez; José Fernando Solanilla-Duque; Emilio Pérez-Pacheco; Jose Herminsul Mina-Hernandez (Polysaccharides, 2025)
Lollipop sticks were developed with fully biobased materials made of different plantain by-products, using extrusion processing followed by hot compression molding. The thermoplastic matrix was constituted of flour and starch from plantain bunch pulp and plantain peel cake. At the same time, two types of reinforcement were used, one of them being yarn from the lignocellulosic fibers of the pseudostem sheaths to constitute the BC1 lollipop stick and the other directly from the plantain pseudostem treated sheath to establish the BC2 lollipop stick. The biobased lollipop sticks were characterized in the migration test, finding a higher structural stability in lipophilic foods, with chocolate chosen as a confection to undergo physicochemical, structural, mechanical, and dynamic–mechanical characterization when interacting with the two biobased lollipop sticks until post-consumption was reached. The BC2 lollipop stick was characterized by maintaining higher stability in maximum tensile strength (12.62 to 11.76 MPa), higher flexural strength (19.07 to 10.11 MPa), storage modulus (4.97 to 1.65 GPa at 30 °C), and Tan delta (66.90 to 52.64 °C).